Change In Bone Mineral Density After Total Ankle Replacement: A Two Year Follow Up - Alkhreisat, Mohammad; Battah, Khairat; RAMASKANDHAN, Jayasree; Alananzh, Mohammad; SIDDIQUE, Malik (Jordan Medical Journal, 2026)
Background: Bone strength around the components is critical for arthroplasty survival. Literature is scarce on changes in bone mineral density (BMD) around total ankle arthroplasty (TAA) designs. This study quantified BMD changes around the components of the uncemented Mobility™ prosthesis preoperatively and postoperatively, while evaluating clinical outcomes. Methods: This prospective study included patients undergoing TAA between March 2008 and April 2009. BMD was measured using the DEXA Hologic® scanner at seven regions of interest (ROIs) around the prosthesis preoperatively and at 1- and 2-year follow-ups. AOFAS scores were also recorded. Results: Twenty-three patients were included. A significant mean BMD decrease (17%, p<0.01) was observed in the lateral malleolus, while the medial tibial metaphysis showed a 7% increase, though not statistically significant. BMD changes at other ROIs were minimal. AOFAS scores improved significantly over the 2 years (p<0.05). Conclusion: Significant BMD loss occurred in the lateral malleolus, likely due to stress shielding. Minimal changes in other regions suggest a stable mechanical environment. Long-term follow-up is necessary to determine the clinical impact of these changes.